ASSESSMENT OF FLOODING IN THE DOWNSTREAM AREA OF KIEN GIANG RIVER BASIN, QUANG BINH PROVINCE BASED ON USING THE MATHEMATICAL MODEL AND REMOTE SENSING TECHNIQUE - Cham, Dao Dinh; Minh, Nguyen Quang; Son, Nguyen Thai; Thao, Dao Thi (Vietnam Journal of Marine Science and Technology, 2017)
Floods frequently occur in the central region in general and in Quang Binh province in particular, including the Kien Giang river basin. In recent years, due to the effects of global climate change and socio-economic development, natural disasters and floods are increasing and threatening the lives of people. This affects the socio-economic development of Quang Binh province. This paper presents the results of a study on the flooding and flooding levels of some typical floods in the downstream area of ​​Kien Giang river, Quang Binh province based on the combination of using MIKEFLOOD model with remote sensing. This is one of the modern research methods that are quite useful in simulating, calculating and forecasting natural disasters occurring in coastal estuaries including floods. Combined use of these two methods yielded, quite accurate and similar results in calculating the flood level and inundation in the Kien Giang river basin. The authors have applied the MIKEFLOOD model to simulate the continuous evolution of inundation processes combined with remote sensing technology to compare and verify the calculation results of the model at the occurrence time of typical floods from 1999 up to now in the study area. The results of this article are the basis for warning and suggesting some measures to prevent flooding before the occurrence of heavy rains in Kien Giang river basin.